RADIATION SAFETY ANALYSIS OF NEUTRON COLIMATOR BASED ON NICKEL MATERIAL FOR PIERCING RADIAL BEAMPORT UTILIZATION OF KARTINI RESEARCH REACTOR (Department of Physics, Faculty of Mathematics and Natural Sciences, 2016)
Radiation safety analysis of nickel material neutron colimator (as requirement) for pearcing radial beamport utilization of Kartini research reactor has been done before the neutron colimator instaled. The neutron collimator made of nickel material with cyllindrical geometry which is 156 cm length. The Inside and outside diameter are 16 cm and 19 cm respectively with mean cyllindrical thickness is 1.5 cm. Irradiation process to the neutron collimator begin when the reactor beeing operated for 6 (six) hours per day and assumed optimum at 100 kW power level. Results of the analysis showed that gamma dose rate which was generated by collimator at a distance of 50 cm from the end of the collimator is 1.5328e-03 mr/hours. The dose rate is still below the dose limit value which was required by Nuclear Energy Regulatory Agency (BAPETEN) is 1 mr/hours. It can be concluded that utilization neutron colimator of nickel material which installed at the radial pierching beamport of Kartini Reactor is safelly.Telah dilakukan kajian analisis keselamatan paparan radiasi terhadap kolimator neutron (sebagai persyaratan) sebelum dipasang pada beamport tembus radial reaktor kartini. Kolimator neutron terbuat dari bahan nikel berbentuk silinder panjang 156 cm dengan diameter dalam 16 cm dan diameter luar 19 cm sehingga tebal silinder 1.5 cm. Proses iradiasi terhadap kolimator neutron terjadi pada saat reaktor dioperasikan pada suatu daya dan diasumsikan optimal pada daya 100 kw selama 6 jam dalam satu hari. Hasil analisis menunjukan laju dosis gamma yang dihasilkan kolimator pada jarak 50 cm dari ujung kolimator sebesar 1.5328e-03 mr/jam. Laju dosis tersebut masih dibawah nilai batas dosis yang ditetapkan oleh bapeten sebesar 1 mr/jam, sehingga penggunaan kolimator tersebut dalam batas aman